2016
DOI: 10.3892/etm.2016.3328
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation effect of Abnormal Savda Munziq on liver and heart toxicity caused by chemotherapy in mice

Abstract: Abstract. Abnormal Savda Munziq (ASMq), an Uighur medicine formula commonly used in the treatment of cancer, has been speculated to possess antioxidative and antiproliferative effects, and to regulate immune activity. The present study was designed to systematically elucidate the toxicity-reducing activity of ASMq in mice undergoing combination chemotherapy with doxorubicin and 5-fluorouracil (5-FU). The mice were divided into normal (saline, 10 ml/kg) and doxorubicin + 5-FU groups (doxorubicin, 2.5 mg/kg; 5-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
3
10
1
Order By: Relevance
“…First, it was previously demonstrated that a similar 5‐FU protocol was not associated with any cellular or functional cardiotoxic effects . Second, the frequency and duration of 5‐FU treatment in the present study were different from other studies reporting the cardiotoxicity of this agent . Third, there was no elevation of ANP or BNP expression in control or swum mice receiving 5‐FU.…”
Section: Discussioncontrasting
confidence: 81%
“…First, it was previously demonstrated that a similar 5‐FU protocol was not associated with any cellular or functional cardiotoxic effects . Second, the frequency and duration of 5‐FU treatment in the present study were different from other studies reporting the cardiotoxicity of this agent . Third, there was no elevation of ANP or BNP expression in control or swum mice receiving 5‐FU.…”
Section: Discussioncontrasting
confidence: 81%
“…On the other hand, luteolin prevented the reduction in spleen and liver weights induced by irinotecan. Chemotherapy toxicity in organs not affected by cancer is one of its limitations (Aikemu et al, ), and the hepatotoxic side effects have been a serious clinical challenge in chemotherapy (Thatishetty, Agresti, & O'Brien, ). In our experiments, irinotecan increases the plasma levels of AST and ALT, whereas luteolin treatment prevented the increase in ALT, findings similar to those of other authors evaluating hepatoprotective effects of this compound (Liu et al, ; He et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, their prolonged use and over dosage cause death. These drugs cause disruption in basal metabolism by showing toxic effect especially in liver and hearth tissues [16]. The biochemical and electron microscopic findings showed that DO x causes he patotoxic effect.…”
Section: Doxorubicin-induced Hepatotoxicitymentioning
confidence: 99%
“…DO x has showed cardiotoxic and hepatotoxic effects in animals. It is known that DOX cause weight loss [13,16]. Thus, their prolonged use and over dosage cause death.…”
Section: Doxorubicin-induced Hepatotoxicitymentioning
confidence: 99%
See 1 more Smart Citation